Penyuluhan Pentingnya Cuci Tangan Yang Baik dan Benar Dalam Upaya Pencegahan Infeksi Cacing di SDN 15 Cakranegara - Ariasti, Mia; Muhsin, Lalu Busyairi; Kurniawan, Salsabila Yunita; Sofya, Sri Winarni; Khaerani, Ayudia Cipta; Novitarini, Novitarini (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
Worm infestation is a parasitic infection that can affect the health, nutrition, intelligence and productivity of patients, especially in primary school-aged children. The disease often occurs due to unsanitary lifestyles and poor sanitation, with a high prevalence in Indonesia, especially in West Nusa Tenggara Province. Children aged 5-14 years, especially in areas with low economic levels, are particularly vulnerable to worms due to a lack of knowledge about clean and healthy living behaviors (PHBS). One solution that can be implemented is to provide counseling to children on how to wash their hands properly to prevent worm infections. This counseling activity was conducted at SDN 15 Cakranegara using a participatory approach, in collaboration with the school and local community. The results of this activity show that counseling can increase children's understanding of the importance of washing hands with soap and running water, which is expected to prevent the spread of worm infections and other related diseases. The success of this counseling is an important step in efforts to increase health awareness among children and communities.